Inferior STEMI as the challenge of predicting the right coronary artery vs. the left circumflex artery as culprit lesion using the ECG criteria: a case report - Fernanda Savitri Mega Pratistha; Ni Luh Eka Sriayu Wulandari (Intisari Sains Medis, 2022)
Background: The morbidity and mortality in Inferior ST-elevation myocardial infarction (STEMI) is also determined by the location of the occlusion. Early Identification of the occlusion site is necessary to assist in the appropriate management of Inferior STEMI. This case study aims to evaluate the Electrocardiogram (ECG) examination, which has a basic role in the diagnosis of STEMI, both in determining the location of myocardial infarction and predicting the location of the culprit lesion. Case Presentation: A 48-year-old male patient complained of dull chest pain, such as being pressured by a heavy object and radiating to the back, followed by nausea, vomiting and cold sweats, and shortness of breath for 2 hours before coming to the hospital. On arrival, the patient was fully conscious with a blood pressure of 110/70 mmHg, pulse rate of 129x/minute with a SpO2 of 95% with electrocardiography (ECG) results showing atrial fibrillation with inferoposterolateral STEMI. Shortly after the ECG examination, the patient became unconscious, with blood pressure dropping to 60/palpation and bradycardia at 48 beats/minute. The patient underwent a fibrinolytic revascularization strategy with Streptokinase 1,500,000 U for 30 minutes, but soon the patient became unconscious with the ECG monitor showing ventricular fibrillation (VF). Hence, cardiopulmonary resuscitation was immediately performed with 360 J defibrillation twice, and the ECG returned to sinus rhythm. After stabilizing, the patient was referred for Rescue Percutaneous Coronary Intervention (PCI). The results of Coronary Angiography showed that the culprit lesion, in this case, was the Left Circumflex Artery with the Right Coronary Artery normal small, and non-dominant. Conclusion: ECG is still an important supporting examination in diagnosing and managing Acute Coronary Syndrome (ACS). An ECG can also help determine the culprit lesion in STEMI before angiography. Inferoposterolateral STEMI can be caused by blockage of the Right Coronary Artery (RCA) or Left Circumflex Artery (LCx).